Shock vibration and damage responses of nuclear island subjected to an aircraft crash. (January 2023) - Sui, Yi; Zou, Degao; Chen, Kai
Abstract: Although more attention has been given towards the analysis of large commercial aircraft impacts since the September 11 attacks, little work has been done on the vibration response of internal structures and equipment of nuclear power plants (NPPs) during an impact. With a focus on new NPPs, this paper develops a remeshing algorithm for contact surfaces, which utilizes the advantages of scaled boundary finite element (SBFE) polyhedral elements to fully realize the potential of Octree and structured grid discretization methods. The vibration response of nuclear island internal structures is examined. The influence of the interaction between the foundation and the structure on the overall dynamic response is analyzed. Meanwhile, different ranges of foundation size are investigated for balance between computational efficiency and accuracy. The vibration propagation mechanism is found by studying the influence of different artificial boundary types and damping conditions of foundation. The results show that the interaction has a significant influence on the vibration response, and that a foundation size of 1B (height of the steel containment vessel) on all sides provides the optimal balance between computational and accuracy requirements. Furthermore, the damping ratio of the foundation plays a key role in vibration propagation. Finally, the combined bonding method is highly flexible, and allows cross-scale integration of different mesh sizes.